Pengaruh Kepemimpinan Inklusif dan Work Life Balance Terhadap Kreativtas Karyawan Dengan Kepuasan Kerja Sebagai Mediasi di PT Bintang Mandiri Medica Selong Lombok Timur - Kristina Mandala Sani; Djoko Suprayetno (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of Inclusive Leadership and Work-Life Balance on Employee Creativity with Job Satisfaction as a Mediation at PT Bintang Mandiri Medica Selong Lombok Timur. The type of research used in this study is causal associative research with a quantitative approach. The data collection method used is the census method. The population in this study were all employees at PT Bintang Mandiri Medica, totaling 45 people. Data were collected through questionnaires and analyzed using SEM-PLS with the assistance of the SmartPls application. The results show that: (1) Inclusive Leadership has a positive and significant effect on Employee Creativity; (2) Work-Life Balance has a positive and significant effect on Employee Creativity; (3) Inclusive Leadership has a positive and significant effect on Job Satisfaction; (4) Work-Life Balance has a positive and significant effect on Job Satisfaction; (5) Job Satisfaction has a positive and significant effect on Employee Creativity; (6) Job Satisfaction is able to significantly mediate the effect of Inclusive Leadership on Employee Creativity; (7) Job Satisfaction is able to significantly mediate the effect of Work-Life Balance on Employee Creativity.